2010
DOI: 10.4102/sajpsychiatry.v16i4.239
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards psychiatry of undergraduate medical students at Bayero University, Nigeria

Abstract: <p><strong>Background</strong>. This study determined and compared responses of 5th- and 6th (final)-year medical students on their attitudes to psychiatry as a profession. Also elicited were their choices of area of future medical specialisation.</p><p><strong>Method</strong>. A prospective and cross-sectional study using an adapted 27-item self-administered questionnaire to obtain responses from 91 5th- and 6th-year medical students at Bayero University, Kano, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Up to a quarter of our study participants, whose mean age was similar to that of another Nigerian study [16,17], considered psychiatry as a possible future career, a finding similar to that of Andlauer and colleagues in France [18] though far higher than that reported by Aghukwa in Nigeria [16]. The determining variables include provision of an exemplary psychiatry clerkship [19], the student's grade in the subject [17,18], and charismatic teaching, mentorship and stigma reduction [10].…”
Section: Discussionsupporting
confidence: 67%
“…Up to a quarter of our study participants, whose mean age was similar to that of another Nigerian study [16,17], considered psychiatry as a possible future career, a finding similar to that of Andlauer and colleagues in France [18] though far higher than that reported by Aghukwa in Nigeria [16]. The determining variables include provision of an exemplary psychiatry clerkship [19], the student's grade in the subject [17,18], and charismatic teaching, mentorship and stigma reduction [10].…”
Section: Discussionsupporting
confidence: 67%
“…To the question, 10% strongly disagreed, 48.2% disagreed, 31.4% were neutral, 15.2% agreed, and 0.5% strongly agreed. This question may involve complex factors, such as views about low status, the patient's treatment effect, income, and others (14)(15)(16).…”
Section: Individual Questions From the Atp-30mentioning
confidence: 99%
“…Enabling us to address the issue of recruitment requires an understanding of not just what attract students and doctors to psychiatry but also what turns them off the speciality. A number of authors from various countries have looked closely at what students' views of psychiatry are [2, 1718] and why those who do look favourably on the speciality as students do not choose to follow it as a career [19]. Feifel et al [2] in a survey of new entrants to US medical schools found that whilst many valued elements of clinical practice that are central to psychiatry, aligning closely with those detailed by Brown et al above, they viewed psychiatry as the least attractive of the various medical specialities asked about.…”
Section: Understanding Why Our Speciality Is Unpopularmentioning
confidence: 99%